2019
DOI: 10.3390/molecules24183350
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Temperature, Ethanol and Cell Wall Material Composition on Cell Wall-Anthocyanin Interactions

Abstract: The effects of temperature and ethanol concentration on the kinetics of anthocyanin adsorption and desorption interactions with five cell wall materials (CWM) of different composition were investigated. Using temperatures of 15 °C and 30 °C and model wine with ethanol concentrations of 0% and 15% (v/v) over 120 min, the adsorption and desorption rates of five anthocyanin-glucosides were recorded in triplicate. Small-scale experiments were conducted using a benchtop incubator to mimic a single berry fermentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…A series of reports have been published in support of a model developed for the extraction of phenolics from red grapes during winemaking, based on experimental data [127][128][129][130][131]. The model was developed as a function of temperature and ethanol concentration, and takes into consideration the release of phenolics, the adsorption of phenolics onto grape material, and the decrease in anthocyanin over time.…”
Section: Effect Of the Grape And Wine Matrixmentioning
confidence: 99%
“…A series of reports have been published in support of a model developed for the extraction of phenolics from red grapes during winemaking, based on experimental data [127][128][129][130][131]. The model was developed as a function of temperature and ethanol concentration, and takes into consideration the release of phenolics, the adsorption of phenolics onto grape material, and the decrease in anthocyanin over time.…”
Section: Effect Of the Grape And Wine Matrixmentioning
confidence: 99%
“…Some release of tannins was observed in the control sample (CW-Tan), attributed to the combined action of ethanol concentration in the model solution and stirring. There are other studies that have looked into the effect of different concentrations of ethanol and different temperatures in the release of cell wall-bound proanthocyanidins and anthocyanidins [ 15 , 18 ]. Beaver et al [ 15 ] carried out desorption tests of cell wall-bound tannins and they showed that, by increasing the ethanol from 0% to 15%, the desorption of the tannins previously absorbed by the cell walls increased significantly, therefore, in the conditions in which we carried out this experiment, part of the tannins absorbed by the cell walls can be released just by the action of ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…Beaver et al [ 15 ] carried out desorption tests of cell wall-bound tannins and they showed that, by increasing the ethanol from 0% to 15%, the desorption of the tannins previously absorbed by the cell walls increased significantly, therefore, in the conditions in which we carried out this experiment, part of the tannins absorbed by the cell walls can be released just by the action of ethanol. On the other hand, Medina-Plaza et al [ 18 ] performed absorption and desorption tests with cell walls and anthocyanins and they also reported that desorption was highly influenced by the temperature and the concentration of ethanol of the medium, even more than by the composition of the cell wall. They stated that possibly, in a real vinification, the wine punches (when there is already ethanol in the medium) may produce a certain release of the tannins and anthocyanins adsorbed by the cellular material in suspension during the maceration.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of anthocyanins, PAs clearly seem to follow Langmuir model assumptions of single-layer adsorption. Anthocyanins, however, have been shown to have some characteristics of multi-layer adsorption likely due to their ability to participate in self-association via π–π stacking [ 14 ]. It is possible that free anthocyanins and polymeric pigment promote multilayer adsorption of PA, increasing the overall adsorptive capacity of the CWM.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the composition and conformation of most cell wall material induce a negative surface charge and that flavylium anthocyanins contain a cationic oxygen on their C-ring, it would stand to reason that the PA–CWM interactions may be disrupted by the presence of the charged anthocyanins. The anthocyanin–CWM interactions would likely be more thermodynamically favorable by comparison to PA–CWM interactions [ 13 , 14 ]. However, the study by Bautista-Ortin et al only studied this phenomenon under a single temperature, ethanol concentration, and PA concentration, all of which could potentially influence the adsorption mechanism or even compositional and conformational changes in PA molecules [ 12 ].…”
Section: Introductionmentioning
confidence: 99%